A Review on Heat Generation and Temperature Distribution Models in Friction stir Welding (FSW). Issue 1 (April 2021) - Singh, Bharat; Sharma, Shailesh; Kumar, Veneet; Maheshwari, Kunal; Singhal, Piyush
Abstract: Nowadays the higher fuel efficiency is a major concern in every developing field of technology and it is also a cause for the development of lightweight materials. There are many applications in which it is required to join two dissimilar lightweight materials. Friction stir welding (FSW) is the most crucial development for such types of applications. This technique helps in overcoming the challenges raised during the joining of two dissimilar materials due to their incompatibility with conventional welding techniques. The lightweight materials developed with the help of friction stir welding (FSW) have applications in various industrial sectors like automotive, electronics, shipbuilding, railways, marine, and many others. It is inevitable in joining the different grades of materials like magnesium alloys, aluminum alloys, and low carbon steels without any weld defect. The thermal properties like heat generation and peak temperature also have a significant effect on the quality and strength of the weld joint. The thermal properties change the microstructure of the weld material and influence the mechanical properties of the welded material. This provides Temperature controlling methods so as to reduce the surface temperature and hence reduce the defects in the welded material. This present review article is based upon the summary of the work carried out by different researchers in the field of thermal modeling of the friction stir welding (FSW).